Learning Analysis In The Interactive Media Design Course For Grade XII At Smkn 9 Garut - ABAD MUKTAFI (RISTEC : Research in Information Systems and Technology, 2025)
Learning Analysis in Class XII Interactive Media Design Subject at SMKN 9 Garut. In analyzing these subjects there are problems faced by teachers and students. The teacher must repeat the material that has been delivered when he wants to carry out the practice, because students often forget the material that has been received before because the students' needs in absorbing the material are different, some understand how to absorb the material by delivering material using the lecture/video tutorial/practice method. , there are even students who will understand the material if the delivery of the material has to combine these three methods. This study aims to optimize the ongoing interactive media design learning process by utilizing technology in interactive media design learning activities. The author uses a descriptive research method. Data collection techniques using Observation Techniques, Interviews, Literature Studies. The analysis model used is the procedural analysis model. The results of the analysis are less flexible learning, lack of visual video assistance and e-tutorials. The final conclusion of this analysis is that it would be nice if the interactive media design learning system for Class XII at SMKN 9 Garut should be made of learning materials based on Android and added video tutorials to assist students in carrying out practical exercises which will impact students more effectively and confidently in doing the exercises. practice.